2-ADIC INTEGRAL CANONICAL MODELS. (5th October 2016) - KIM, WANSU; MADAPUSI PERA, KEERTHI
Abstract : We use Lau's classification of 2-divisible groups using Dieudonné displays to construct integral canonical models for Shimura varieties of abelian type at 2-adic places where the level is hyperspecial.